Pengabdian Sebagai Dewan Juri Bidang Teknik Desain Laman Lomba Kompetensi Siswa (LKS) SMK Tingkat Provinsi Kalimantan Utara Tahun 2025 - Novita Ranti Muntiari; Denis Prayogi (LPPM Universitas Harapan Bangsa Purwokerto, 2025)
Student Competency Competition is an annual competition between students at the vocational high school level according to the areas of expertise taught at participating vocational schools. This LKS is equivalent to the OSN (National Science Olympiad) held in junior high schools/high schools. This activity is one part of a series of selections to get the best students from all over Indonesia who will be further guided by their respective competition field teams and will be included in international level expertise competitions. The purpose of the community service activities carried out through this LKS competition activity is for the Community Service Team to contribute as a jury in the Page Design Technique competition. The role of the jury is very important as the determinant of the final results of the provincial level LKS, so that the best students can represent North Kalimantan Province to compete at the national level. The final result of this community service activity is an official decision from the jury on the competition assessment process in determining the winner of the 2025 North Kalimantan Provincial Level SMK LKS.